PERANCANGAN HUNIAN VERTIKAL SEBAGAI TEMPAT TINGGAL, BERKREASI, DAN BERINSPIRASI - Coreen Katrina Tania; Fermanto Lianto (Jurusan Arsitektur dan Perencanaan, 2022)
With the continuous increase of population growth in urban life but not the availability of comparable urban land for housing, the demand for apartments becomes a solid investment. Vertical housing has much capacity and can create green open space in a vertical environment. The emergence of a new lifestyle of living and working forms a new residence based on the characteristics of generations. This paper examines the effect of changes in lifestyle that are no longer conventional on the development of vertical housing, namely living and working housing. Using the biophilic method as an effort to approach nature with spaces. The biophilic concept is a concept that shows the relationship between the natural environment and humans in the hope of being able to influence the physical and psychological conditions of the user. Applying the biophilic concept seeks to create an expected atmosphere or condition, which can provide opportunities for humans/users to live and work healthy, reduce users' stress levels, and have an inspiring and prosperous living environment by using designs closer to nature. The purpose of this paper is to find a new residential typology to deal with changing lifestyles in this generation related to the need for adequate housing in dense areas. That's why the construction of